Survival of dogs with myxomatous mitral valve disease administered preclinical pimobendan in comparison to pimobendan-naïve dogs from the onset of congestive heart failure - G. McAulay; M. Hills; J. Dukes-McEwan; E. Dutton; A. Jakubczak; D. Singleton; E. Bode; W. Yangwanitset; M. Hezzell (Journal of Veterinary Cardiology, 2026)

To Cook or Not to Cook: Correlates of Meal Preparation Enjoyment - Danielle J. Gartner; Paul L. Hutchinson; Chelsea R. Singleton (Journal of Nutrition Education and Behavior, 2026)

Triple oxygen and hydrogen stable isotope composition of water in Murchison carbonaceous chondrite accessed by thermogravimetry-enabled laser spectroscopy - Erik J. Oerter; Alexandre Garenne; Miguel Cisneros; George D. Cody; Michael Singleton; Conel M. O’D. Alexander (Chemical Geology, 2025)

Sodic-calcic alteration and transpressional shear along the Atacama fault system during IOCG mineralization, Copiapó, Chile - N. M. Seymour; J. S. Singleton; R. Gomila; G. Arancibia; J. Ridley; M. L. Gevedon; D. F. Stockli; S. M. Seman (Mineralium Deposita, 2024)
The Punta del Cobre district near Copiapó is a center of iron oxide-copper–gold (IOCG) mineralization spatially and temporally associated with regional sodic-calcic hydrothermal alteration, the Atacama fault system (AFS), and two phases of Early Cretaceous magmatism. Here, we investigate the spatiotemporal and geochemical relationships between magmatism, ductile deformation, and hydrothermal alteration along the ~ 200 to 300-m-thick steeply NW-dipping Sierra Chicharra shear zone, interpreted to be the major strand of the AFS. Mylonitic fabrics and oblique sinistral-reverse kinematic indicators together record coaxial flattening in a transpressional regime. Deformation on the AFS took place before, during, and after intrusion of the synkinematic Sierra Chicharra quartz diorite of the Coastal Cordillera arc at ~ 122 Ma and terminated before intrusion of the unstrained ~ 114 Ma Sierra Atacama diorite of the Copiapó batholith. Geochemical data show that the Copiapó batholith was more mafic and more K-rich than the calc-alkaline Coastal Cordillera arc. This time period thus overlaps IOCG mineralization in the Punta del Cobre district (~ 120 to 110 Ma). Multiple phases of sodic-calcic alteration in and around the AFS shear zone are recognized. Textures of altered rock in the shear zone show both synkinematic assemblages and post-kinematic hydrothermal oligoclase. A ~ 775-m-long andradite vein that cuts the shear zone formed broadly at the end of magmatism in the district (~ 95 Ma). Oxygen isotope ratios from the vein indicate that hydrothermal fluids were likely magmatically derived. Together, this work shows the AFS-related shear zone and nearby IOCG mineralization developed in a regional transpressional regime produced by SE-directed oblique convergence across a NE-striking shear zone. IOCG-related magmatic-hydrothermal fluids exploited this transcrustal shear zone to produce multiple episodes of regional sodic-calcic alteration formed from fluids exsolved from magmas or driven by the heat of the Coastal Cordillera arc and Copiapó batholith.

Reconciling species conservation and ecosystem resilience: Northern spotted owl habitat sustainability in a fire-dependent forest landscape - Joshua S. Halofsky; Daniel C. Donato; Peter H. Singleton; Derek J. Churchill; Garrett W. Meigs; William L. Gaines; Jonathan T. Kane; Van R. Kane; Danielle Munzing; Paul F. Hessburg (Forest Ecology and Management, 2024)

Casting a wider net: A national survey of Australian attitudes to marine protected areas - Nyree L. Raabe; Tanya J. King; Adam P.A. Cardilini; Kelly K. Miller; Shaun Bangay; Andrew Singleton (Ocean & Coastal Management, 2024)

Frankia diversity in sympatrically occurring red alder (Alnus rubra) and Sitka alder (Alnus viridis) trees in an early successional environment - Emily R. Wolfe; Sebastian Singleton; Nathan U. Stewart; Mehmet A. Balkan; Daniel J. Ballhorn (Trees, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Alien introgression and morpho-agronomic characterization of diploid progenies of Solanum lycopersicoides monosomic alien addition lines (MAALs) toward pre-breeding applications in tomato (S. lycopersicum) - Puneet Kaur Mangat; Junghyun Shim; Ritchel B. Gannaban; Joshua J. Singleton; Rosalyn B. Angeles-Shim (Theoretical and Applied Genetics, 2021)
Key message Alien introgressions that were captured in the genome of diploid plants segregating from progenies of monosomic alien addition lines of S. lycopersicoides confer novel phenotypes with commercial and agronomic value in tomato breeding. Abstract Solanum lycopersicoides is a wild relative of tomato with a natural adaptation to a wide array of biotic and abiotic challenges. In this study, we identified and characterized diploid plants segregating from the progenies of monosomic alien addition lines (MAALs) of S. lycopersicoides to establish their potential as donors in breeding for target trait improvement in tomato. Molecular genotyping identified 28 of 38 MAAL progenies having the complete chromosome complement of the cultivated tomato parent and limited chromosome introgressions from the wild S. lycopersicoides parent. Analysis of SSR and indel marker profiles identified 34 unique alien introgressions in the 28 MAAL-derived introgression lines (MDILs) in the genetic background of tomato. Conserved patterns of alien introgressions were detected among sibs of MDILs 2, 3, 4 and 8. Across MDILs, a degree of preferential transmission of specific chromosome segments was also observed. Morphologically, the MDILs closely resembled the cultivated tomato more than S. lycopersicoides . The appearance of novel phenotypes in the MDILs that are lacking in the cultivated parent or the source MAALs indicates the capture of novel genetic variation by the diploid introgression lines that can add commercial and agronomic value to tomato. In particular, screening of representative MDILs for drought tolerance at the vegetative stage identified MDIL 2 and MDIL 11III as drought tolerant based on visual scoring. A regulated increase in stomatal conductance of MDIL 2 under drought stress indicates better water use efficiency that allowed it to survive for 7 days under 0% moisture level.

The early Palaeogene transition from thin-skinned to thick-skinned shortening in the Potosí uplift, Sierra Madre Oriental, northeastern Mexico - Stewart A. Williams; J. S. Singleton; M. G. Prior; S. P. Mavor; G. E. Cross; D.F. Stockli (International Geology Review, 2021)

Genetic risk factors in Parkinson’s disease - K. J. Billingsley; S. Bandres-Ciga; S. Saez-Atienzar; A. B. Singleton (Cell and Tissue Research, 2018)

Evidence for rapid, tide-related shifts in the microbiome of the coral Coelastrea aspera - M. J. Sweet; B. E. Brown; R. P. Dunne; I. Singleton; M. Bulling (Coral Reefs, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Nucleus incertus promotes cortical desynchronization and behavioral arousal - Sherie Ma; Giancarlo Allocca; Emma K. E. Ong-Pålsson; Caitlin E. Singleton; David Hawkes; Stuart J. McDougall; Spencer J. Williams; Ross A. D. Bathgate; Andrew L. Gundlach (Brain Structure and Function, 2017)

Using wavelet tools to analyse seasonal variations from InSAR time-series data: a case study of the Huangtupo landslide - R. Tomás; Z. Li; J. M. Lopez-Sanchez; P. Liu; A. Singleton (Landslides, 2016)

Early harvest of monsoon rice to address seasonal hunger in northwest Bangladesh - Florencia G. Palis; Arelene J. B. Malabayabas; Grant R. Singleton; Mohammed A. Mazid; David E. Johnson (Food Security, 2016)

Reconstructing the demographic history of orang‐utans using Approximate B ayesian Computation - Alexander Nater; Maja P. Greminger; Natasha Arora; Carel P. van Schaik; Benoit Goossens; Ian Singleton; Ernst J. Verschoor; Kristin S. Warren; Michael Krützen (Molecular Ecology, 2015)
Investigating how different evolutionary forces have shaped patterns of DNA variation within and among species requires detailed knowledge of their demographic history. O rang‐utans, whose distribution is currently restricted to the S outh‐ E ast A sian islands of B orneo ( P ongo pygmaeus ) and S umatra ( P ongo abelii ), have likely experienced a complex demographic history, influenced by recurrent changes in climate and sea levels, volcanic activities and anthropogenic pressures. Using the most extensive sample set of wild orang‐utans to date, we employed an Approximate B ayesian Computation ( ABC ) approach to test the fit of 12 different demographic scenarios to the observed patterns of variation in autosomal, X ‐chromosomal, mitochondrial and Y ‐chromosomal markers. In the best‐fitting model, Sumatran orang‐utans exhibit a deep split of populations north and south of L ake T oba, probably caused by multiple eruptions of the T oba volcano. In addition, we found signals for a strong decline in all S umatran populations ~24 ka, probably associated with hunting by human colonizers. In contrast, B ornean orang‐utans experienced a severe bottleneck ~135 ka, followed by a population expansion and substructuring starting ~82 ka, which we link to an expansion from a glacial refugium. We showed that orang‐utans went through drastic changes in population size and connectedness, caused by recurrent contraction and expansion of rainforest habitat during Pleistocene glaciations and probably hunting by early humans. Our findings emphasize the fact that important aspects of the evolutionary past of species with complex demographic histories might remain obscured when applying overly simplified models.

Connectivity Planning to Address Climate Change - TRISTAN A. NUÑEZ; JOSHUA J. LAWLER; BRAD H. MCRAE; D. JOHN PIERCE; MEADE B. KROSBY; DARREN M. KAVANAGH; PETER H. SINGLETON; JOSHUA J. TEWKSBURY (Conservation Biology, 2013)
As the climate changes, human land use may impede species from tracking areas with suitable climates. Maintaining connectivity between areas of different temperatures could allow organisms to move along temperature gradients and allow species to continue to occupy the same temperature space as the climate warms. We used a coarse‐filter approach to identify broad corridors for movement between areas where human influence is low while simultaneously routing the corridors along present‐day spatial gradients of temperature. We modified a cost–distance algorithm to model these corridors and tested the model with data on current land‐use and climate patterns in the Pacific Northwest of the United States. The resulting maps identified a network of patches and corridors across which species may move as climates change. The corridors are likely to be robust to uncertainty in the magnitude and direction of future climate change because they are derived from gradients and land‐use patterns. The assumptions we applied in our model simplified the stability of temperature gradients and species responses to climate change and land use, but the model is flexible enough to be tailored to specific regions by incorporating other climate variables or movement costs. When used at appropriate resolutions, our approach may be of value to local, regional, and continental conservation initiatives seeking to promote species movements in a changing climate. Planificación de Conectividad para Atender el Cambio Climático

Avian Urine: Its Potential as a Non-Invasive Biomonitor of Environmental Metal Exposure in Birds - J. B. Clapp; R. M. Bevan; I. Singleton (Water, Air, & Soil Pollution, 2012)

Submarine Groundwater Discharge-Derived Nutrient Loads to San Francisco Bay: Implications to Future Ecosystem Changes - Kimberly A. Null; Natasha T. Dimova; Karen L. Knee; Bradley K. Esser; Peter W. Swarzenski; Michael J. Singleton; Mark Stacey; Adina Paytan (Estuaries and Coasts, 2012)

Relations of hydrogeologic factors, groundwater reduction-oxidation conditions, and temporal and spatial distributions of nitrate, Central-Eastside San Joaquin Valley, California, USA - Matthew K. Landon; Christopher T. Green; Kenneth Belitz; Michael J. Singleton; Bradley K. Esser (Hydrogeology Journal, 2011)

Meta-analysis of the acute effects of nicotine and smoking on human performance - Stephen J. Heishman; Bethea A. Kleykamp; Edward G. Singleton (Psychopharmacology, 2010)

Variability in the characteristics of cut‐off low pressure systems over subtropical southern Africa - A. T. Singleton; C. J. C. Reason (International Journal of Climatology, 2007)
Variability in the characteristics of cut‐off low pressure systems over subtropical southern Africa is examined for the 1973–2002 period. These characteristics include their seasonality, frequency, duration, location and size. It is found that on average 11 cut‐off lows occur over southern Africa south of 20°S per year and are most common in the March‐May season. Potential relationships between the number of cut‐off lows over southern Africa with the El Niño Southern Oscillation (ENSO), the Pacific South America pattern, the wave number 3 pattern and the semi‐annual oscillation (SAO) are discussed. La Niña years appear to be associated with above average annual frequencies of cut‐off lows but the reverse is generally not true for El Niño years. There was a shift in the preferred season for cut‐off lows from March–May to June–August in the 1980s, which coincided with a weakening of the SAO and a shift in zonal wave number 3. This period also showed a change in the preferred location of these systems from southwestern subtropical southern Africa to the northeast of the region. The results suggest that there may be a relationship between cut‐off lows over subtropical southern Africa, the wave number 3 pattern in the Southern Hemisphere and the SAO. Copyright © 2006 Royal Meteorological Society.

The major features of an infestation by the invasive weed legume gorse (Ulex europaeus) on volcanic soils in Hawaii - J. K. Leary; N. V. Hue; P. W. Singleton; D. Borthakur (Biology and Fertility of Soils, 2006)

Is reproduction of the Australian house mouse (Mus domesticus) constrained by food? A large-scale field experiment - Hannu Ylönen; Jens Jacob; Myfanwy J. Runcie; Grant R. Singleton (Oecologia, 2003)

DMT1: A mammalian transporter for multiple metals - Michael D. Garrick; Kevin G. Dolan; Craig Horbinski; Andrew J. Ghio; Dennis Higgins; Michael Porubcin; Elizabeth G. Moore; Lucille N. Hainsworth; Jay N. Umbreit; Marcel E. Conrad; Lee Feng; Agnieska Lis; et al. (BioMetals, 2003)

Cloning, expression, and characterization of pyrrolidone carboxyl peptidase from the archaeon Thermococcus litoralis - M. R. Singleton; S. J. C. Taylor; Julian S. Parrat; J. A. Littlechild (Extremophiles, 2000)

Anthropogenic radionuclides in tide-washed pastures bordering the Irish Sea coast of England and Wales - A. L. Sanchez; A. D. Horrill; B. J. Howard; D. Singleton; K. Mondon (Water, Air, & Soil Pollution, 1998)

Similarities in the behaviour of Chernobyl derived Ru-103, Ru-106 and Cs-137 in two freshwater lakes - J. Hilton; W. Davison; J. Hamilton-Taylor; M. Kelly; F. R. Livens; E. Rigg; D. L. Singleton (Aquatic Sciences, 1994)